Fuel performance analysis of reduced moderated boiling water reactor for transuranic waste incineration. (July 2021) - Sukjai, Yanin; Shirvan, Koroush
Abstract: Reduced moderated boiling water reactors (BWR) could serve as near-term alternative to sodium fast reactors for the application of transuranic waste incineration. One such concept currently proposed by Hitachi is the Resource-Renewable Boiling Water Reactor for Transuranic Burning (RBWR-TB2) that utilizes the proven advanced BWR (ABWR) technology. FRAPCON-3.5 EP with its capability to model the physical phenomena at high temperature and high burnup conditions is used to compare the fuel performance of RBWR-TB2 and ABWR fuel rods. The comparison suggests that because of high axial peaking factors and relatively flat power history, fuel temperature is significantly higher in fissile zones of the RBWR-TB2 leading to higher fission gas release and cladding deformation. The higher local fuel burnup in fissile zones of RBWR-TB2 also leads to large but acceptable fuel swelling, accelerated cladding oxidation, and PCMI. In order to assist future design optimizations, sensitivity analyses on important fuel design parameters are also performed. Highlights: A fuel performance comparison between the RBWR-TB2 and the ABWR fuel rods has been performed. Fuel temperature is higher in fissile zones of the RBWR-TB2 because of high axial peaking factors and flat power history. Using annular fuel geometry and more hypostoichiometric fuel could reduce fuel temperature at high burnup. For more resistance to cladding corrosion and PCMI, it is suggested to increase cladding thickness and decrease fuel density.